Method to develop social impact pathways: A case on carbon- and steel reinforced concrete - Alexandra Weniger; Arij Mohamad Radwan Omar Chabrawi; Marzia Traverso (Developments in the Built Environment)
This research aims present a new approach to perform type II Social Life Cycle Assessments (S-LCAs), impact pathways (IP), applied to Carbon- and Steel Reinforced Concrete. The application of IP requires determining causal relations and characterization factors. However, the literature indicates to persistent deficiencies in identifying empirical cause-effect relations and scientific development of characterization factors. To advance IP application, a new approach by using structural equation modeling (SEM) to develop IP is presented in this research. Primary data was collected by questioning workers based on 8 inventory indicators for 3 social subcategories. The results showed where the causal relations could be empirically proven or not, indicating that is suitable for creating social IPs based on real cause-effect chain. For future research, it is recommended to apply the developed model on a larger sample to verify the proposed method and discuss the extent to which complex social issues can be generalized.